Energy generation through bioelectrochemical degradation of pentachlorophenol in microbial fuel cell. Issue 37 (6th June 2018) - Khan, Nishat; Khan, M. Danish; Nizami, Abdul-Sattar; Rehan, Mohammad; Shaida, Azfar; Ahmad, Anees; Khan, Mohammad Z.
Abstract : Bio-electrochemical degradation of pentachlorophenol was carried out in single as well as dual chambered microbial fuel cell (MFC) with simultaneous production of electricity. Abstract : Bio-electrochemical degradation of pentachlorophenol was carried out in single as well as dual chambered microbial fuel cell (MFC) with simultaneous production of electricity. The maximum cell potential was recorded to be 787 and 1021 mV in single and dual chambered systems respectively. The results presented nearly 66 and 89% COD removal in single and dual chambered systems with corresponding power densities of 872.7 and 1468.85 mW m −2 respectively. The highest coulombic efficiency for single and dual chambered counterparts was found to be 33.9% and 58.55%. GC-MS data revealed that pentachlorophenol was more effectively degraded under aerobic conditions in dual-chambered MFC. Real-time polymerase chain reaction showed the dominance of exoelectrogenic Geobacter in the two reactor systems with a slightly higher concentration in the dual-chambered system. The findings of this work suggested that the aerobic treatment of pentachlorophenol in cathodic compartment of dual chambered MFC is better than its anaerobic treatment in single chambered MFC in terms of chemical oxygen demand (COD) removal and output power density.